Tracking Problem-Solving Behavior in One-Dimensional Kinematics: A Study of Physics Education Undergraduates - Suci Rizkina Tari; Fitria Herliana; Fadiya Haya (Universitas Lambung Mangkurat, 2026)
A qualitative study was employed to explore undergraduate Physics Education students’ behavior during problem-solving of one-dimensional kinematics. Six undergraduate students from Physics Education program were chosen as the participants. The main data for this research were gathered through the think-aloud technique, which involved recording participants’ verbalizations, transcribing, and coding the data. This analysis was further supported by observations, interviews, and students’ written responses. The study identified twenty-four distinct behaviors commonly exhibited by students when solving problems related to one-dimensional kinematics. These behaviors included initial reading, repeated reading, strategic reading, organizing information, clarifying the problem context, drawing a visual representation, recalling relevant knowledge, identifying the goal, selecting the appropriate formula, identifying the variable, developing the plan, formulating a sub-plan, linking the concept, considering the formula, considering the variable, checking the plan, checking the computation, estimating the answer, recognizing error, evaluating the plan, reflecting on themselves, performing basic calculation, performing algebra, and presenting or writing down the solution. These behaviors were categorized into eight broader groups, which allowed for a clearer interpretation of students' behavior during problem-solving. The eight categories of behavior revealed in this study align with Polya’s four-step problem-solving model and Schoenfeld’s theory of metacognition. The results offer meaningful insights into the ways students interpret, plan, and evaluate solutions to physics problems. The findings also provide important implications for physics education by offering insights that lecturers can use to design learning instruction that explicitly supports the development of students’ problem-solving skills. Future research is suggested to design targeted interventions that support the development of expert-like problem-solving in undergraduate physics education based on the results of this study.